2009
DOI: 10.1073/pnas.0806821106
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific integration of adeno-associated virus involves partial duplication of the target locus

Abstract: A variety of viruses establish latency by integrating their genome into the host genome. The integration event generally occurs in a nonspecific manner, precluding the prediction of functional consequences from resulting disruptions of affected host genes. The nonpathogenic adeno-associated virus (AAV) is unique in its ability to stably integrate in a site-specific manner into the human MBS85 gene. To gain a better understanding of the integration mechanism and the consequences of MBS85 disruption, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…Transgene integration inito the AAVS1 locus reduces MBS85 expression at the mRNA level, but this reduction can be avoided by modifying the transgene [4]. Pluripotent stem cells with exogenous DNA inserted into the AAVS1 locus show normal phenotype and differentiation potential [5,6]. However, misgivings have arisen because the function of MBS85 is not yet completely understood [1].…”
Section: Introductionmentioning
confidence: 99%
“…Transgene integration inito the AAVS1 locus reduces MBS85 expression at the mRNA level, but this reduction can be avoided by modifying the transgene [4]. Pluripotent stem cells with exogenous DNA inserted into the AAVS1 locus show normal phenotype and differentiation potential [5,6]. However, misgivings have arisen because the function of MBS85 is not yet completely understood [1].…”
Section: Introductionmentioning
confidence: 99%
“…These viral vectors are nonreplicating and well tolerated in rodents. AAV is a safer viral vector, as it is less likely to induce insertional mutagenesis and has a low immune response [176]. Thus, AAV2 has been commonly and safely used in a number of human clinical trials, including treatments for Parkinson's and Alzheimer's diseases [177,178].…”
Section: Translational Potential Of Optogenetics and Limitationsmentioning
confidence: 99%
“…Interestingly, most of the AAV serotypes have three contiguous repeats flanked by pseudo-repeats, a feature that is shared with AAVS1 (18). The site-specific integration process is contingent on the presence of the large regulatory proteins Rep78/Rep68, the AAVS1 site, and a cis-acting viral DNA sequence (1,17,19,20). Earlier studies reported that for the AAVS1 region a minimum sequence of 33 bp containing the RBS and trs sequences is essential for site-specific integration (16,17,21).…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%
“…The requirement of site-specific nicking of the AAVS1 trs site suggests that some of the steps resemble the terminal resolution reaction during AAV DNA replication. This process is a variation of the mechanism used by DNA relaxases during DNA conjugation (20,24,25). The first step in site-specific integration is the assembly of a Rep78/ Rep68-DNA complex guided by the recognition of GCTC repeats through the N-terminal origin-binding domain (OBD).…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%
See 1 more Smart Citation